Audit of Cesarean Section Rates and Indications in Public Sector Hospitals of Saudi Arabia - Ali, Zahra Elbukhari Mohammed Ahmed; Jamali, Sanam (Biological and Clinical Sciences Research Journal, 2025)
The global rise in cesarean section (CS) rates has raised concerns about its appropriateness and potential overuse. Understanding local trends and clinical indications is essential for optimizing obstetric practices. Objective: To audit the rates and clinical indications of cesarean section deliveries in selected public sector hospitals of Saudi Arabia. Methods: This retrospective, multi-center clinical audit was conducted over six months (October 2023 to March 2024) in three major government hospitals: King Saud Medical City (Riyadh), King Fahd Hospital of the University (Al Khobar), and Maternity and Children Hospital (Jeddah). 1,050 CS cases (350 from each hospital) were included using non-probability consecutive sampling. Inclusion criteria were women aged 18–45 who underwent elective or emergency CS during the study period. Data were extracted from medical records, including maternal age, parity, booking status, gestational age, type and indication of CS, comorbidities, and neonatal outcomes. Statistical analysis was performed using SPSS Version 26.0. Associations between CS type and clinical parameters were tested using chi-square, with p < 0.05 considered significant. Results: The mean maternal age was 30.8 ± 5.7 years; 58.9% were multiparous. Elective and emergency CS accounted for 44% and 56% of cases, respectively. The most common indications were previous CS (28%), fetal distress (18.9%), and cephalopelvic disproportion (12%). A significant association (p < 0.001) was found between the type of CS and its indication. Emergency CS was linked to lower Apgar scores (p = 0.003) and low birth weight (p = 0.041). No significant institutional difference was observed in CS types across hospitals (p = 0.078). Conclusion: Cesarean section rates in public hospitals of Saudi Arabia exceed WHO recommendations, with prior CS and fetal distress being the leading indications. Institutional practices were consistent, but clinical vigilance is needed to reduce unnecessary CS.